2020
DOI: 10.1021/acs.jchemed.0c00725
|View full text |Cite
|
Sign up to set email alerts
|

Delivering High School Chemistry During COVID-19 Lockdown: Voices from Africa

Abstract: This paper provides glimpses of transactions in chemistry classrooms in five African countries (Burundi, Ghana, Morocco, Nigeria, and Senegal) during the COVID-19 lockdown. Members of the secondary school community in the countries including teachers, students, and school managers were unprepared for the unprecedent demand in shift from a face-to-face to an online delivery system. From a tepid, faltering start in the early days of the lockdown in Morocco, Nigeria, and Senegal, and recognizing that the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…33% of studies (n = 27) had between one and 25 participants, which represents a higher percentage of smaller scale studies than in higher education research (16%, . Three studies did not report the exact number of participants involved (Education Scotland, 2021;Okebukola et al, 2020;Rusmansyah et al, 2021).…”
Section: Figure 5 Year Levels Representedmentioning
confidence: 99%
See 2 more Smart Citations
“…33% of studies (n = 27) had between one and 25 participants, which represents a higher percentage of smaller scale studies than in higher education research (16%, . Three studies did not report the exact number of participants involved (Education Scotland, 2021;Okebukola et al, 2020;Rusmansyah et al, 2021).…”
Section: Figure 5 Year Levels Representedmentioning
confidence: 99%
“…Over two-fifths of studies reported behavioural disengagement among students (n = 36, 44%), with absence being the most common expression of behavioural disengagement (n = 15, 19%). In some cases, issues with technology, such as problems with connectivity, were found to impact student attendance (e.g., Okebukola et al, 2020). In some other cases teachers and parents stated that students clicked on links to participate in live lessons but then became distracted with other activities (e.g., Bhattarai, 2020).…”
Section: Behavioural Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59). Further papers address some specific impacts of the pandemic, such as on education (60,61), transport (62), quality of life and wellbeing (63)(64)(65), and environmental pollution (66)(67)(68). Ouhsine et al (69) analyze the impacts of the pandemic on solid waste generation at Moroccan households.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, some students cannot even attend online classes because, especially in developing counties with digital inequality, they do not have access to digital devices (Khlaif & Salha, 2020). Following the closure of schools, the rapid change from classroom to online teaching heavily influenced not only the learners but also the instructors (Okebukola, 2020). Instructors received immediate tasks in regard to "implementing distance learning modalities" (United Nations, 2020), such as having courses on online platforms, as the schools started to close due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%